2018
DOI: 10.3390/ijerph15071421
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Sustainable Spent Mushroom Waste Adsorbent Based on Surfactant Modification for the Removal of Toxic Dyes

Abstract: The treatment of wastewater always demands eco-friendly and cost-efficient adsorbents. In this paper, spent mushroom waste (SMW) was modified by a cationic surfactant (cetyltrimethylammonium bromide, CTAB) to eliminate toxic dyes. A characterization of adsorbents confirmed that CTAB was successfully embedded into the SMW structure. The spent mushroom waste, modified by CTAB (SMWC), exhibited an excellent adsorption capacity of 249.57 mg·g−1, 338.67 mg·g−1, and 265.01 mg·g−1 for the Direct red 5B (DR5B), Direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 59 publications
(56 reference statements)
0
20
0
Order By: Relevance
“…The adsorption was suitable with the Langmuir isotherm model due to the highest correlation value. Similarly, Alhujaily et al [ 42 ] indicated that the anionic textile dye biosorption by a cationic surfactant‐modified mushroom waste was best fitted with the Langmuir model. The Langmuir isotherm model shows the homogeneous surface of the biosorbent covering with a single layer.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption was suitable with the Langmuir isotherm model due to the highest correlation value. Similarly, Alhujaily et al [ 42 ] indicated that the anionic textile dye biosorption by a cationic surfactant‐modified mushroom waste was best fitted with the Langmuir model. The Langmuir isotherm model shows the homogeneous surface of the biosorbent covering with a single layer.…”
Section: Resultsmentioning
confidence: 99%
“…The rate-limiting factor assumed by quasi-secondary reaction kinetics was consistent with the results obtained by thermodynamic analysis. Moreover, the intraparticle diffusion was probably not a control factor during the adsorption process [13].…”
Section: Resultsmentioning
confidence: 99%
“…The specific surface area of the adsorbent was measured by a Brunner–Emmet–Teller (BET) measurement (QuadraSorb SI, Quantachrome, Boynton Beach, FL, U.S.) [12]. X-ray diffraction spectroscopy (XRD) was used with an X-ray diffraction spectrometer (D8-Advance, Bruker, Karlsruhe, Germany) [13]. The tube pressure was 20 KV, the scanning range was 5–60°, and the scanning speed was 0.02°/0.2 s. The substance contained therein was determined based on the diffraction database.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports have shown that mushroom residue contains a large amount of crude protein, minerals, amino acids, and other active nutrients. It can be considered a potential high-quality, unconventional raw material for livestock and poultry feed [4,5]. At present, most mushroom residue is burned for power generation or discarded, while only a small proportion is processed for animal feed, wasting a precious biological resource and causing serious ecological damage to the environment [6].…”
Section: Introductionmentioning
confidence: 99%